PENGARUH FAKTOR-FAKTOR EKSTERNAL DAN INTERNAL TERHADAP KINERJA USAHA KECIL DAN MENENGAH DI JAKARTA - Alex Sandra; Edi Purwanto (Universitas Bunda Mulia, 2017)
This study aims to analyse: (1) the effect of external factors on internal factors of SMEs; (2) the effect of external factors on SMEs performance; and (3) the effect of internal factors on SMEs performance in Jakarta. The result show that: (1) the external factors has positive and significant impact on internal factors of SMEs, (2) the external factors has positive but unsignificant on SMEs performance, and (3) the internal factors has positive and significant on SMEs performance in Jakarta. Keywords: Small and Medium Enterprises, External factors, Internal factors, SMEs performance